Users' experiences of an online intervention for bipolar disorder: important lessons for design and evaluation. Issue 4 (23rd October 2017) - Dodd, Alyson L; Mallinson, Sara; Griffiths, Martin; Morriss, Richard; Jones, Steven H; Lobban, Fiona
Abstract : Background: The evidence base for digital interventions for physical and mental health, including severe and enduring mental health difficulties, is increasing. In a feasibility trial, web-based Enhanced Relapse Prevention (ERPonline) for bipolar disorder demonstrated high recruitment and retention rates. Relative to participants in the waitlist control group, those who received ERPonline showed increased monitoring for early warning signs of relapse and had developed more positive illness models. Objective: To understand users' motivations and barriers for taking part in an online/telephone-based trial, and for engagement with ERPonline. Methods: Participants from the trial who had been allocated to receive ERPonline were purposively sampled to participate in telephone-based, in-depth qualitative interviews about their experiences. Interviews (n = 19) were analysed using framework analysis to identify themes relevant to study aims. Findings: Participants took part due to the convenient, flexible and rewarding aspects of the trial design, as well as a desire to improve the mental health of themselves and others. Barriers included extensive assessments, practical difficulties and mood. ERPonline was was generally considered to be accessible, relevant and straightforward, but there were individual preferences regarding design, content and who it was for. Several participants reported positive changes, but there was a sense that digital interventions should not replace routine care. Conclusions: There are a number of barriers and facilitators to consider when evaluating and implementing digital interventions. Individual preferences and human contact were key factors for both trial design and engagement with an online intervention. Clinical implications: Digital interventions should be co-produced, personalised, interactive and embedded as one component in a broader package of care. Trial registration number: ISRCTN56908625; Post-results.